Influence of the Valsalva maneuver on cardiac hemodynamics and right to left shunt in patients with patent foramen ovale - Zhao, Enfa (Sci Rep, 2017)
The purpose of this study was to investigate the influence of the Valsalva maneuver (VM) on cardiac hemodynamics in patients with patent foramen ovale (PFO). Sixty-five patients who were highly suspected to have PFO were included. The changes in E, A, E/A ratio of mitral valve blood flow, E, A, E/A ratio of tricuspid valve blood flow, left ventricular end-diastolic volume, area and right atrial area during the resting state and the strain phase of the Valsalva maneuver were observed by transthoracic echocardiography (TTE). Statistical analyses were performed using SPSS Version18.0. Compared to the resting state, mitral valve diastolic velocity E and A peaks at the strain phase of the Valsalva maneuver significantly decreased (P < 0.05), left ventricular end diastolic volume(LVEDV) and area(LVEDA) decreased significantly (P < 0.05), while E/A ratio of mitral valve, tricuspid valve systolic velocity E and A peaks and E/A ratio remained unchanged (P > 0.05). PFO hemodynamic changes mainly occurred in the left ventricle when the Valsalva maneuver was performed. The Valsalva maneuver increased pressure in the chest, then pulmonary venous return was impeded, which resulted in left ventricular limited filling, and E and A peaks decreased. The pressure of the left ventricle and atrium was lower than that of the right side, which resulted in right-to-left shunt (RLS) through PFO.